Evaluasi Hasil Histerosalpingografi Pasien Infertil dengan Nyeri dan Laparoskopi di Rumkital Dr. Ramelan Surabaya - Nanda Putra Prakasa; Mita Herdiyantini; Dody Taruna (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT Background: Infertility can caused factors of cervix, uterine, tubal and peritoneal, ovulation and sperm factors in men. Abnormality of tubal factor and primary peritoneum factors are endometriosis and PID, which clinically give complain of pain. Checkup of tubal and peritoneum factors are difficult to conduct. It needs laparoscopic equipment and laparoscopic specialist doctors. Whereas the most convenient, cheapest, not invasive and large equipment which are used to find tubal factor is by checking-up Hysterosalpingography (HSG). HSG only can find tubal potential and peritoneal factor. Objective: to measure the relation between pain and checkup result of hysterosalpingography with laparoscopic examination results. Method: observational analytic which was retrospective longitudinal using secondary data and medical record infertile women who had been conducted HSG test before, which were conducted laparoscopy and registered in obstetrician at Rumkital dr. Ramelan Surabaya in Januari 2013 - December 2017 as population. The samples were 30 respondents. Furthermore, data analysis were calculated using Chi-square test, Fisher Exact Test. It was carried out the descriptive analysis for data by valuing Sensitivity, Specificity, Positive Predictive Value and Negative Divination Value. Result: data showed that there was relation between pain and the result of laparoscopy test in infertile patient and there was relation between the result of HSG test and the result of laparoscopy test in infertile paitients at Rumkital dr. Ramelan Surabaya. Conclusion: there is a relation between pain complain and the result of hysterosalpingography with laparoscopic examination results.